GATA4 loss in the septum transversum mesenchyme promotes liver fibrosis in mice. - Delgado, Irene; Carrasco, Manuel; Cano-Rincón, Elena; Carmona-Mejías, Rita María; García-Carbonero, Rocío; Marín-Gómez, Luis M.; Soria, Bernat; Martín, Francisco; Cano, David A.; Muñoz-Chápuli-Oriol, Ramón; Rojas, Anabel (AASLD, 2014)
The zinc finger transcription factor GATA4 controls specification and differentiation of multiple cell types during embryonic development. In mouse embryonic liver, Gata4 is expressed in the endodermal hepatic bud and in the adjacent mesenchyme of the septum transversum. Previous studies have shown that Gata4 inactivation impairs liver formation. However, whether these defects are caused by loss of Gata4 in the hepatic endoderm or in the septum transversum mesenchyme remains to be determined. In this study, we have investigated the role of mesenchymal GATA4 activity in liver formation. We have conditionally inactivated Gata4 in the septum transversum mesenchyme and its derivatives by using Cre/loxP technology. We have generated a mouse transgenic Cre line, in which expression of Cre recombinase is controlled by a previously identified distal Gata4 enhancer. Conditional inactivation of Gata4 in hepatic mesenchymal cells led to embryonic lethality around mouse embryonic stage 13.5, likely as a consequence of fetal anemia. Gata4 knockout fetal livers exhibited reduced size, advanced fibrosis, accumulation of extracellular matrix components and hepatic stellate cell (HSC) activation. Haploinsufficiency of Gata4 accelerated CCl4-induced liver fibrosis in adult mice. Moreover, Gata4 expression was dramatically reduced in advanced hepatic fibrosis and cirrhosis in humans. Conclusions: Our data demonstrate that mesenchymal GATA4 activity regulates HSC activation and inhibits the liver fibrogenic process.
https://openpolicyfinder.jisc.ac.uk/id/publication/13950
Keywords: Factores de transcripción; Hígado - Enfermedades; Hígado - Fibrosis - Modelos animales; Gata4; Liver; Fibrosis; Septum transversum